River capture processes and it's relation with Paleogeographical development in the central part of Syrian coastal chain - إبراهيم, سعيد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
In this research we discussed Paleogeographical development, which had exposed to, the western part of Syria through 2nd and 3d age, and explained the reaction of this development and rising movements, for which had exposed Syrian coastal chain in it's present form, giving a 2 kinds of river valleys (dip and strike), caused a lot of river capture accidents, resulting of water division line transition, leading to changing the adjacent river basins area. This accidents has influents on it's hydrological recharge, and geomorphological, morphometrical characteristics. In the results, we could define riverine capture accidents, which accompanied with forming 2 main strike valleys named "Wadi Johannam and Wadi Jdeideh-Borjileh" with another river capture areas and expected ones.